Criopreservación de espermatozoides: citoesqueleto, balsas lipídicas e integridad nucleoproteíca (2021)
This work aimed to carry out an approach through literature review of the main damages in the cytoskeleton, plasma membrane lipid rafts and the sperm nucleus caused by cryopreservation procedures. For this purpose, a search was carried out in different databases: Pub Med, Elsevier, CAB abstract and Google Scholar, with previously defined keywords. forty-three articles were obtained, which were analyzed and discussed in the literature review. The alteration in the cytoskeletal structure of spermatozoa caused by cryopreservation procedures is associated with the cryocapacitation phenomenon or “premature capacitation” of the same, expressed in increased Factin polymerization. Lipid rafts are microdomains present in the plasma membrane and play an important role in the regulation of signal transmission in sperm. It has been found that cryopreservation produces irreversible aggregation of proteins, some of these associated with lipid rafts and it is hypothesized that the lipid rafts are affected preventing their movement towards the sperm apical zone, which results in a reduction in the fertilizing ability. Cryopreservation affects the degree of chromatin condensation, produces DNA fragmentation and changes in important genes. In conclusion, this review provides important information that allows an alternative emphasis to be made to the damage of the plasma membrane reviewed by other authors, providing evidence of the damage to the cytoskeleton, lipid rafts and the sperm nucleus caused by cryopreservation.